Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41598-021-88379-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two established 2D staging techniques to their appliance in 3D cone beam computer-tomography for dental age estimation

Abstract: For medicolegal purposes, orthodontic or orthognathic treatment various stomatological staging technique for age estimation with appliance of conventional radiographic images have been published. It remains uninvestigated if cone beam computer-tomography delivers comparable staging results to the conventional radiographic stages of third molar analysis. We conducted a retrospective cross-sectional study of 312 patients aged 13–21 years. Dental age estimation staging technique, introduced by Nolla and Demirjian… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
5
0
3
Order By: Relevance
“…Examples of Nolla’s stages 5, 6, 7, 8 and 9 are demonstrated in Figure 1 . Nolla stage 8 is described as having two-thirds of the root completed [ 9 , 10 ], and the tooth has emerged into the oral cavity. Therefore, the primary tooth was considered retained when its successor permanent tooth was in Nolla stage 8 and below the alveolar crypt, Nolla stage 9 or Nolla, stage 10.…”
Section: Methodsmentioning
confidence: 99%
“…Examples of Nolla’s stages 5, 6, 7, 8 and 9 are demonstrated in Figure 1 . Nolla stage 8 is described as having two-thirds of the root completed [ 9 , 10 ], and the tooth has emerged into the oral cavity. Therefore, the primary tooth was considered retained when its successor permanent tooth was in Nolla stage 8 and below the alveolar crypt, Nolla stage 9 or Nolla, stage 10.…”
Section: Methodsmentioning
confidence: 99%
“…Diversos métodos são empregados para estimativa de idade em crianças e adolescentes (Gelbrich et al, 2019, Kuhnen et al 2021. O método de Nolla e Demirjian, através da classificação dos estágios de mineralização dentária, permitem determinar a idade cronológica de indivíduos (Nolla, 1960;Demirjian et al, 1973;Ginzelova et al, 2019;Zirk et al, 2021). No entanto, ambos os métodos são aplicados em imagens bidimensionais (Zirk et al, 2021).…”
Section: Estimativa De Idade Em Crianças E Adolescentesunclassified
“…O método de Nolla e Demirjian, através da classificação dos estágios de mineralização dentária, permitem determinar a idade cronológica de indivíduos (Nolla, 1960;Demirjian et al, 1973;Ginzelova et al, 2019;Zirk et al, 2021). No entanto, ambos os métodos são aplicados em imagens bidimensionais (Zirk et al, 2021). Ginzelova et al (2019) compararam a idade cronológica com a idade dentária em crianças através do método de Demirjian usando radiografias panorâmicas ou TCFC.…”
Section: Estimativa De Idade Em Crianças E Adolescentesunclassified
See 1 more Smart Citation
“…[35][36][37] Some previous studies have demonstrated the advantages of CBCT in estimating dental age based on metric measurements in adults and children. [38][39][40][41] Some recent studies have investigated the use of CBCT to estimate the age of children and adults. [40][41][42][43][44] To the best of our knowledge, no studies have been conducted on the accuracy of I 3M for dental age estimation in adolescents and young adults using CBCT.…”
mentioning
confidence: 99%